2018
DOI: 10.3390/app8010134
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Fe3O4 Nanoparticles and Chemotherapeutic Agents on Prostate Cancer Cells In Vitro

Abstract: Abstract:Patients with metastatic castration-resistant prostate cancer (mCRPC) have poor outcomes. Docetaxel (DTX)-based therapy is a current standard treatment for patients with mCRPC. Approaches combining conventional chemotherapeutic agents and nanoparticles (NPs), particularly iron oxide NPs, may overcome the serious side effects and drug resistance, resulting in the establishment of new therapeutic strategies. We previously reported the combined effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This study demonstrated that Fe hours resulted in a signi cant inhibition of cell viability with different inhibitory effects [24]. Various studies have demonstrated that the mechanism of apoptosis by metal nanoparticles pertains to affecting ROS interactions in the treated cells [26 − 25].…”
Section: Discussionmentioning
confidence: 81%
“…This study demonstrated that Fe hours resulted in a signi cant inhibition of cell viability with different inhibitory effects [24]. Various studies have demonstrated that the mechanism of apoptosis by metal nanoparticles pertains to affecting ROS interactions in the treated cells [26 − 25].…”
Section: Discussionmentioning
confidence: 81%
“…Yeh et al presented an H 2 O 2 -loaded ultrasound contrast agent H 2 O 2 /Fe 3 O 4 -poly(D,L-lactide-co-glycolic acid (PLGA) polymersome, which could yield sufficient • OH through the Fenton reaction of encapsulated H 2 O 2 and Fe 3 O 4 , completely removing the malignant tumors in a non-thermal process (Li et al, 2016 ). Watanabe et al investigated the combined effects of Fe 3 O 4 nanoparticles with chemotherapeutic agents (rapamycin or carboplatin) on prostate cancer cells in vitro (Kojima et al, 2018 ). Synergistic effect of Fe 3 O 4 NPs was observed in DU145 cells with carboplatin and in PC-3 cells with rapamycin, increasing intracellular ROS levels to decrease cancer cell viability significantly.…”
Section: Ferrite-based Ros-mediated Cancer Therapymentioning
confidence: 99%
“…Bahadur et al developed PEGylated mesoporous iron platinum-iron oxide composite nanoassemblies with high loading capacity of doxorubicin, which exhibited a higher efficiency of ROS generation compared to Fe 3 O 4 and Pt under the synergistic catalytic effect of FePt and Fe 3 O 4 , resulting in efficient chemo-and thermal therapy for Hela cancer cells (Sahu et al, 2015 (Li et al, 2016). Watanabe et al investigated the combined effects of Fe 3 O 4 nanoparticles with chemotherapeutic agents (rapamycin or carboplatin) on prostate cancer cells in vitro (Kojima et al, 2018). Synergistic effect of Fe 3 O 4 NPs was observed in DU145 cells with carboplatin and in PC-3 cells with rapamycin, increasing intracellular ROS levels to decrease cancer cell viability significantly.…”
Section: Intrinsic Fenton Reaction Of Ferritementioning
confidence: 99%
“…These particles are coated with a biocompatible polymer to enhance their stability and cell transfer effects [15,16]. SPION-based drug delivery, nano-biomaterial, bio-imaging, and other methods are studied to determine their practical applications, and animal studies have been conducted to determine their potential in SCI therapy by using stem-cell-fusion to increase migration [17,18]. However, further studies are needed before SPIONs can be applied clinically and to demonstrate the migration, stability, and safety by magnetic induction of stem cell fusions [19,20].…”
Section: Introductionmentioning
confidence: 99%